2015
DOI: 10.1117/12.2083026
|View full text |Cite
|
Sign up to set email alerts
|

Content-aware video quality assessment: predicting human perception of quality using peak signal to noise ratio and spatial/temporal activity

Abstract: Since the end-user of video-based systems is often a human observer, prediction of human perception of quality (HPoQ) is an important task for increasing the user satisfaction. Despite the large variety of objective video quality measures, one problem is the lack of generalizability. This is mainly due to the strong dependency between HPoQ and video content. Although this problem is well-known, few existing methods directly account for the influence of video content on HPoQ. This paper propose a new method to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…First, we perform an extensive experimental evaluation based on a total of four VQMs, each tested on 696 distorted video sequences. The four tested VQMs comprise three newly presented here [structural similarity index measure (SSIM), 27 standardized method for objectively measuring video quality (SOVQM), 7 and video quality assessment by decoupling detail losses and additive impairments (VQAD) 10 26. Second, we describe the differences between the proposed methodology and other state-of-the-art methodologies which explicitly include content related indexes in their computation.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…First, we perform an extensive experimental evaluation based on a total of four VQMs, each tested on 696 distorted video sequences. The four tested VQMs comprise three newly presented here [structural similarity index measure (SSIM), 27 standardized method for objectively measuring video quality (SOVQM), 7 and video quality assessment by decoupling detail losses and additive impairments (VQAD) 10 26. Second, we describe the differences between the proposed methodology and other state-of-the-art methodologies which explicitly include content related indexes in their computation.…”
Section: Introductionmentioning
confidence: 99%
“…This can be seen as a disadvantage of their approach knowing that PVQ is affected by both spatial and temporal content related indexes 13 and that previous works have shown that PVQ and PSNR is better modeled by using an S-shape function which takes into account the saturation effect of the human vision. 15,26,31 Khan et al…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations